IMPLEMENTATION OF HEALTH PROTOCOLS IN PREVENTION OF COVID-19 DISEASE IN LOK BAITAN VILLAGERS - Alit Suwandewi (UMBanjarmasin, 2021)
The case of COVID-19 caused by the corona virus (SARS-Cov-2) continues to experience a significant increase in Indonesia, People are urged to stay indoors to break the chain of spreading Covid -19, but under certain conditions we still have to leaving the house to do activities, in order to stay safe and avoid infection, the ministry of health makes a health protocol as a solution. Lok baitan village, Sungai Tabuk sub-district is a densely populated village with an inadequate level of compliance with health protocols, thus creating vulnerability to transmission. The team conducted education to add insight and knowledge to the people of Lok Baitan village, Sungai Tabuk District, to always implement health protocols in the prevention of Covid-19 and the team also provided COVID-19 prevention assistance to overcome the limited means of prevention in the area.